2004
DOI: 10.1523/jneurosci.4537-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

Independent Coding of Reward Magnitude and Valence in the Human Brain

Abstract: Previous research has shown that two components of the event-related brain potential, the P300 and feedback negativity, are sensitive to information about rewards and penalties. The present study investigated the properties of these components in a simple gambling game that required participants to choose between cards that were unpredictably associated with monetary gains and losses of variable magnitude. The aim was to determine the sensitivity of each component to two critical features of reward stimuli: ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

129
916
26
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 853 publications
(1,073 citation statements)
references
References 14 publications
129
916
26
2
Order By: Relevance
“…To explain this finding, one might propose that reward processing, at least of abstract financial reinforcers, is rather coarse in nature, providing a discrete evaluation of events as good or bad regardless of magnitude. Similar results have been reported for the feedback negativity (Holroyd et al, 2004a;Yeung and Sanfey, 2004). In contrast, the results seem inconsistent with a recent study that found a parametric ordering (in terms of both timing and magnitude) of the BOLD responses in left caudate nucleus to the magnitude of monetary gains and losses (Delgado et al, 2003).…”
Section: Discussioncontrasting
confidence: 59%
“…To explain this finding, one might propose that reward processing, at least of abstract financial reinforcers, is rather coarse in nature, providing a discrete evaluation of events as good or bad regardless of magnitude. Similar results have been reported for the feedback negativity (Holroyd et al, 2004a;Yeung and Sanfey, 2004). In contrast, the results seem inconsistent with a recent study that found a parametric ordering (in terms of both timing and magnitude) of the BOLD responses in left caudate nucleus to the magnitude of monetary gains and losses (Delgado et al, 2003).…”
Section: Discussioncontrasting
confidence: 59%
“…Presumably, this is because of a general preference for certain information over uncertain information, which results in the “ambiguity aversion” phenomenon on the behavioral level (Ho et al., 2002; Payzan‐LeNestour & Bossaerts, 2011). In addition, it is worth noting that the FRN is sensitive to the relevance of an ongoing event to behavioral adjustments (Holroyd, Baker, Kerns, & Muller, 2008; Pfabigan, Alexopoulos, Bauer, & Sailer, 2010; Yeung & Sanfey, 2004). From this perspective, the larger FRN following ambiguous magnitude may indicate a stronger motivation to seek unambiguous information, in order to reduce the uncertainty of the current scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the authors aim to investigate how ambiguity in outcome feedback is reflected in brain activity. Two major dimensions that characterize outcome feedback are valence and magnitude (Litt, Plassmann, Shiv, & Rangel, 2011; Yeung & Sanfey, 2004). The valence dimension indicates whether a stimulus is desirable, which is positive for rewards and negative for punishments (Litt et al., 2011; Paton, Belova, Morrison, & Salzman, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations